Peningkatan Kemampuan Membaca Pemahaman Siswa Melalui Model Cooperative Integrated Reading and Composition (CIRC) di Kelas IV SDN 05 Tarok Dipo Kota Bukittinggi - Anggun Syahrani; Ari Suriani; Adrias Adrias; Chandra (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Elementary school students' reading comprehension ability in descriptive text learning is still relatively low, especially in the reorganization and inferential aspects. This study aims to improve the reading comprehension ability of fourth grade students through the application of the Cooperative Integrated Reading and Composition (CIRC) model. The study used Classroom Action Research with qualitative and quantitative approaches implemented in two cycles and three meetings through the stages of planning, action implementation, observation, and reflection. The study was conducted at SDN 05 Tarok Dipo, Bukittinggi City with one teacher and 27 fourth grade students as subjects. Data collection was carried out through observation, reading comprehension tests, and documentation. Qualitative data were analyzed by reviewing the results of observations of teacher and student activities to see changes in the learning process, while quantitative data were analyzed using percentage techniques to determine the increase in learning outcomes in each cycle. The results showed an increase in the quality of learning planning and teacher and student activeness. Students' reading comprehension ability at the reorganization level increased from 77% to 92%, while inferential ability increased from 55% to 87%. Thus, the application of the CIRC model has proven effective in improving fourth grade students' reading comprehension ability in descriptive text learning.